Determining the optimal isoleucine:lysine ratio in diets for the segregated early-weaned pig - J R Bergstrom; J A Loughmiller; R E Musser; W B Nessmith Jr; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
A 14-d growth trial was conducted to evaluate effects of increasing isoleucine: lysine ratios on growth performance of the segregated early-weaned pig. Twelve experimental diets included two levels of lysine (1.15%and 1.50% digestible lysine) and six digestible isoleucine: lysine ratios (40, 45,50, 55, 60, and 65% relative to lysine) in a 2 x 6 factorial arrangement. From d 0 to 14, growth performance was improved by feeding 1.50% digestible lysine. A linear improven1ent in growth performance occurred from d 0 to 7 as the isoleucine:lysine ratio increased. Although a significant quadratic response was not observed, little improvement in pig performance occurred above the 60% apparent digestible isoleucine: lysine ratio. Increasing isoleucine had no effect on the overall growth perforn1ance from d 0 to 14, but plasma urea nitrogen (PUN) was linearly reduced on d 14. These data suggest that the isoleucine requirement for the SEW pig is approximately 60% of lysine on an apparent digestible basis. However, because this response was observed only in the first week postweaning, further research is required to confirm this high a requirement for isoleucine.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Early-weaned pigs; Amino acid; Isoleucine